Pulmonary Segmentectomy with Tunneling Stapler Technique - Kobayashi, Naohiro; Endo, Katsuyuki (The Thoracic and Cardiovascular Surgeon, 2014)
Pulmonary segmentectomy necessitates dissection of the lung parenchyma. Stapling is one method of dissecting the lung parenchyma. However, simple stapling of the segmental plane might result in restriction of residual lung inflation and a short margin from the lesion. Therefore, a technique of segmental plane dissection via staple incisions radially spreading out from the segmental bronchus stump has been developed, which is made possible by creating a tunnel passageway to maneuver the stapler's anvil. This procedure can reduce restriction of lung inflation and secure surgical margins from the lesion.
Keywords: lung cancer treatment; surgery/equipment; surgery/incisions